Faktor yang Berhubungan dengan Pengelolaan Sampah Rumah Tangga di Kecamatan Danau Teluk Kota Jambi - Afrida Setia Ningsih; Sugiarto Sugiarto (Universitas Veteran Bangun Nusantara, 2020)
Based on data from the Jambi City Environmental Service, it is known that from 11 Districts in Jambi City, the percentage of landfills in Teluk Teluk District is in the first place, which is 71%. The research objective was to determine the factors associated with household waste management in Danau Teluk District, Jambi City. This research is a quantitative study with a cross sectional design. The research sample was 94 housewives who lived in Danau Teluk District, Jambi City using simple random sampling technique. This study was analyzed by univariate and bivariate analysis using the chi-square test. The instrument used was a questionnaire. The results showed that as many as 76.6% of respondents had good knowledge, 21.3% had sufficient knowledge and 2.1% had low knowledge, 91.5% of respondents had good facilities and infrastructure and 8.5% had good facilities and infrastructure. poor infrastructure, 75.5% of respondents have high motivation and 24.5% have low motivation and 60.6% have a role in the role of health workers while 39.4% do not play a role of health workers. The results of the bivariate analysis show that there is no relationship between knowledge (0.631) and facilities and infrastructure (0.911), while for the motivation variable (0.001) and the role of officers (0.002) there is a relationship with household waste management in Danau Teluk District, Jambi City in 2020. encouragement or support from family, closest people and health workers or the local government or local government to be able to advocate / invite the community to no longer be accustomed to littering or burning garbage to be behavior that pays more attention to the surrounding environment